2020
DOI: 10.1017/s0029665120000063
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in western dwelling South Asian populations: an unrecognised epidemic

Abstract: Vitamin D deficiency (25-hydroxyvitamin D; 25(OH)D) is at epidemic proportions in western dwelling South Asian populations, including severe deficiency (<12⋅5 nmol/l) in 27–60% of individuals, depending on season. The paper aimed to review the literature concerning vitamin D concentrations in this population group. Research from the UK and Europe suggests a high prevalence of South Asians with 25(OH)D concentration <25 nmol/l, with most having a 25(OH)D concentration of <50 nmol/l. In Canada, South As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 80 publications
2
19
0
1
Order By: Relevance
“…A meta-analysis of 394 cross-sectional studies showed a correlation between vitamin D levels and latitude in Caucasians (−0.69 ± 0.30 nmol l −1 per degree, p = 0.02), but not for non-Caucasians (0.03 ± 0.39 nmol l −1 per degree, p = 0.14) [ 12 ]. Vitamin D deficiency (low serum 25(OH)D) is very common in western dwelling South Asian populations, including very severe deficiency (less than 12.5 nmol l −1 ) in 27–60% of individuals [ 13 ]. Although seasonal variation in vitamin D is found, a study from Birmingham, UK showed that 94% were vitamin D deficient in winter and 82% in summer [ 14 ].…”
Section: People With Dark Skin Who Are Obese Who Are Elderly or Whomentioning
confidence: 99%
“…A meta-analysis of 394 cross-sectional studies showed a correlation between vitamin D levels and latitude in Caucasians (−0.69 ± 0.30 nmol l −1 per degree, p = 0.02), but not for non-Caucasians (0.03 ± 0.39 nmol l −1 per degree, p = 0.14) [ 12 ]. Vitamin D deficiency (low serum 25(OH)D) is very common in western dwelling South Asian populations, including very severe deficiency (less than 12.5 nmol l −1 ) in 27–60% of individuals [ 13 ]. Although seasonal variation in vitamin D is found, a study from Birmingham, UK showed that 94% were vitamin D deficient in winter and 82% in summer [ 14 ].…”
Section: People With Dark Skin Who Are Obese Who Are Elderly or Whomentioning
confidence: 99%
“…Vitamin D deficiency and insufficiency is a global phenomenon, and it has been estimated that approximately 60% of adults worldwide are vitamin D deficient and insufficient (Daly et al, 2012). It is known that Vitamin D deficiency is particularly prevalent in South Asian, including severe deficiency (<12.5 nmol/l) up to 27-60% of individuals (Darling, 2020). In India, vitamin D deficiency prevails in epidemic proportions, with a prevalence of 70%-100% in the general population (Ritu and Ajay, 2014).…”
Section: Effect Of Vitamin D Deficiency On Liver Cancer Riskmentioning
confidence: 99%
“…Regardless of the season when the samples were taken, median serum 25(OH)D concentrations for Indian, Pakistani and Bangladeshi participants were all close to, or below 25 nmol/L, with summer concentrations being only slightly higher than during other seasons (22) . During winter and spring, approximately 60% of participants had a serum Accepted manuscript nmol/L; 20% had 25(OH)D <15 nmol/L.…”
Section: Vitamin D Status In Ethnic Minority Groupsmentioning
confidence: 87%
“…Data from the 2010 Health Survey for England has also highlighted that Asian participants (over 16 years) had a lower mean 25(OH)D status (20.5 nmol/L) than White participants (45.8 nmol/L) (20) . Dr Darling presented findings from a secondary analysis of data from the UK Biobank cohort (2006-2010) on the determinants of 25(OH)D status for South Asian adults (Indian, Pakistani and Bangladeshi) living in the UK, including information on serum 25(OH)D concentration as well as vitamin D dietary intakes and supplement use (21,22) . The cohort comprises over 500,000 people, aged 40-69 years old, among whom are 8024 participants of South Asian ethnicity.…”
Section: Vitamin D Status In Ethnic Minority Groupsmentioning
confidence: 99%